Prosocial Behavior and Student Resilience in the Context of Pata Dela Culture: A Study of Senior High School Students in Ngada, Indonesia - Stefanus Lio; Dhiu Margaretha; Enasely Mega Wenyi Rohi; Gracianus Edwin Tue P. Lejap; Carmelita Meno Gara (Universitas PGRI Yogyakarta, 2026)
Resilience is an essential capability that needs to be developed in students to cope with academic and social pressures. Prosocial behavior is considered a factor that can potentially enhance students’ resilience through positive interpersonal interactions. This study aimed to analyze the effect of prosocial behavior on students’ resilience within the context of the Pata Dela culture. A quantitative approach with a survey design was employed. The study involved 119 students, selected using purposive sampling. The sample was limited to students from the Pata Dela cultural background, so the findings may not be widely generalizable. The instruments used included the Prosocial Behavior Scale (Caprara et al., 2005) and the Resilience Scale (Connor & Davidson, 2003). Data were analyzed using simple linear regression. The results indicated that prosocial behavior had a positive and significant effect on student resilience (B = 0.856; t = 7.887; p < 0.001), with a coefficient of determination (R²) of 0.347. This suggests that prosocial behavior accounted for 34.7% of students’ resilience, while the remaining 65.3% was influenced by other factors beyond this study. The findings highlight that the values of the Pata Dela culture serve as a social context that strengthens the relationship between prosocial behavior and resilience. This study contributes to understanding how integrating local cultural contexts, such as Pata Dela, can inform the relationship between prosocial behavior and student resilience, a relationship that has been rarely explored. Keywords: prosocial behavior, resilience, students, pata dela culture